A preparation method and application of anti-icing agent based on silicon dioxide
Through the silicon dioxide-based anti-ice agent preparation method, the problem of poor anti-ice effect of existing anti-ice coatings under harsh conditions is solved, and the effect of low ice adhesion strength and prolonging freezing time in harsh environments is achieved.
Patent Information
- Application Number
- CN202310895780.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-07-20
AI Technical Summary
现有防冰涂料在恶劣低温或阴天条件下防冰效果不佳,且超疏水表面的冰粘附强度在多次结冰/除冰过程后显著增加,限制了其应用。
Using a silicon dioxide-based anti-ice agent preparation method, a uniform anti-ice coating was formed by mixing ethyl acetate, FAST-17 and SiO2 nanoparticle powder, adding epoxy resin and fluorosilicone resin, and using an epoxy resin curing agent.
Without energy consumption, the ice adhesion strength is greatly reduced, the freezing time is extended, and the good anti-icing effect is maintained in a harsh low temperature and high humidity environment.
Smart Images

Figure CN117070122B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating preparation, and specifically relates to a preparation method of an anti-icing agent based on silicon dioxide and application thereof. Background Art
[0002] In principle, anti-icing coatings can be roughly divided into three categories: electrothermal, photothermal and hydrophobic.
[0003] The electrothermal coating contains conductive materials, which makes the coating layer form a semiconductor material and prevents ice by generating electric heat through the action of a small leakage current on the surface of the object. Chuan Jun et al. developed a composite inorganic carbon electrothermal coating with excellent electrothermal performance. When the temperature is (19±2)℃ and the voltage is 36V, the surface temperature of the coating can reach 299℃ after 18 minutes of power on. This solves the problems of low heating temperature, slow heating and poor heat resistance of traditional electrothermal coatings. Ai Xiaolong et al.
[25] studied the effect of different conductive fillers on the electrothermal performance of electrothermal coatings, and showed through electrothermal performance tests and SEM analysis that graphite is an excellent conductive filler for carbon electrothermal coatings. The anti-icing method of electrothermal coatings is not stable enough. If the current on the surface of the object is too small, it cannot meet the heat required for anti-icing; when the current is large, it will cause more losses.
[0004] Photothermal anti-icing coatings are mainly composed of pigments that can absorb light and heat and a highly hydrophobic base material, and use the absorbed light and heat to achieve the purpose of anti-icing. Hu Xiaohua and others developed a new type of photothermal coating using modified silica sol-styrene acrylic emulsion as the base material and FeMnCuOx with excellent light absorption properties as the pigment. Through experiments, it was found that the coating has a good anti-icing effect on unpowered aluminum wires in an environment of -20 to 0°C. The effect of photothermal coatings mainly depends on weather conditions. If it is a sunny day with strong light, the photothermal anti-icing coating has a good anti-icing effect, but in rainy weather, the effect of the coating will be greatly reduced.
[0005] Since the discovery of the "lotus effect", superhydrophobic surfaces have received increasing attention both in academic research and in industrial applications. Pan et al. designed a new three-scale micro / nanostructure superhydrophobic surface by combining a hybrid method of ultrafast laser ablation and chemical oxidation. This new surface structure consists of a periodic micro-bone array, on which densely grown "nanograss" and dispersed "nanoflower" structures are covered. Droplets have excellent Cassie-Baxter stability on this surface. Due to the multi-level complex structure on the surface, its minimum ice adhesion strength can be reduced to 1.7 kPa. However, due to the poor mechanical stability of the micro-nanostructure, the micro-nanostructure is worn after multiple icing / deicing processes, causing the droplets to embed in the micro-nanostructure, and the ice adhesion strength of the superhydrophobic surface increases significantly after only 5 icing / deicing cycles. The adhesion between the microstructure and the droplets greatly limits the application of superhydrophobic surfaces. Based on the current situation that it is difficult to achieve anti-icing under severe low temperatures or cloudy conditions, superhydrophobic surfaces have significant use value and prospects. Summary of the invention
[0006] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an anti-icing agent based on silicon dioxide.
[0009] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing an anti-icing agent based on silicon dioxide, comprising the following steps:
[0010] Mix the main ingredients: Mix ethyl acetate and FAST-17, then add SiO2 nanoparticle powder and stir to mix evenly;
[0011] Add resin: add epoxy resin and fluorosilicone resin and mix well;
[0012] Adding resin curing agent: Add epoxy resin curing agent and stir well to prepare silica-based anti-icing agent.
[0013] As a preferred embodiment of the method for preparing the silicon dioxide-based anti-icing agent of the present invention, the weight of the SiO2 nanoparticle powder in the mixed main material is 5-50% of the total weight of the system.
[0014] As a preferred embodiment of the method for preparing the silicon dioxide-based anti-icing agent of the present invention, in the mixed main materials, the weight of the SiO2 nanoparticle powder is 40% of the total weight of the system.
[0015] As a preferred embodiment of the method for preparing the silicon dioxide-based anti-icing agent of the present invention, the particle size of the SiO2 nanoparticle powder is 7 to 40 nm.
[0016] As a preferred embodiment of the method for preparing the silicon dioxide-based anti-icing agent of the present invention, the ratio of ethyl acetate to FAST-17 is 25:0.8 by weight.
[0017] As a preferred embodiment of the method for preparing the silicon dioxide-based anti-icing agent of the present invention, the resin and the resin curing agent are added and mixed evenly by using magnetic stirring at a stirring speed of 300 revolutions per minute.
[0018] As a preferred embodiment of the method for preparing the silicon dioxide-based anti-icing agent of the present invention, in the mixed main ingredients, the mixing is carried out by stirring and ultrasonic dispersion, and the ultrasonic dispersion has a frequency of 20 kHz, a power of 500 watts, and an operating temperature of 25°C.
[0019] Another object of the present invention is to provide a use of a silicon dioxide-based anti-icing agent.
[0020] To solve the above technical problems, the present invention provides the following technical solutions: an application of a silica-based anti-icing agent, which comprises: placing the silica-based anti-icing agent in a spray device and spraying it on a glass material to form a silica-based anti-icing coating.
[0021] As an application of the silica-based anti-icing agent of the present invention, it includes: the nozzle diameter is 1.5, 2, 3 mm, the spraying pressure is controlled at 0.1 to 0.5 MPa, the spraying distance is maintained at 5 to 30 cm, and the spraying time is 5 to 60 s.
[0022] As an application of the silicon dioxide-based anti-icing agent of the present invention, it includes: spraying on glass material with a nozzle diameter of 2 mm, a spraying pressure of 0.3 MPa, a spraying distance of 20 cm, and a spraying time of 30 seconds
[0023] Beneficial effects of the present invention:
[0024] The present invention provides a waterproof coating given with silicon dioxide, which can significantly reduce the ice adhesion strength and prolong the freezing time without consuming energy, and also has an anti-icing effect in a harsh low-temperature and high-humidity working environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0026] Figure 1 The microstructure micrographs of the coatings with different SiO2 nanoparticle mass fractions in Example 2 of the present invention are shown;
[0027] In the figure, Figure a is a fiber structure diagram of SiO2 5%; Figure b is a fiber structure diagram of SiO2 10%; Figure c is a fiber structure diagram of SiO2 20%; Figure d is a fiber structure diagram of SiO2 40%; Figure e is a fiber structure diagram of SiO2 50%;
[0028] Figure 2 The contact angle and the rolling angle of the water droplets formed by spraying SiO2 nanoparticles with different mass fractions on the glass to form a coating in Example 2 of the present invention;
[0029] Figure 3 The freezing time and ice adhesion strength of water droplets placed on glass and coating in Example 4 of the present invention. DETAILED DESCRIPTION
[0030] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0031] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0033] The silicon dioxide used in the embodiment of the present invention is silicon dioxide produced by Shanghai MacLean Biochemical Co., Ltd., and has a particle size of 7 to 40 nm.
[0034] Example 1
[0035] The present invention is used to prepare a waterproof coating, and the specific preparation method is as follows:
[0036] 1. Place 25 parts of ethyl acetate and 0.8 parts of FAS-17 in a beaker;
[0037] 2. After adding different masses of SiO2 nanoparticle powder (nanopowder dosage is 40%), magnetic stirring (magnetic stirring speed is 400 rpm) and ultrasonic dispersion are performed for 10 min each (frequency 20 khz, power 500 watts, operating temperature 25°C);
[0038] 3. Add 4 parts of epoxy resin (GCC135) and 3 parts of fluorosilicone resin (provided by Chengdu Aikoda Chemical Reagent Co., Ltd.), and stir magnetically for 25 minutes; (speed 300 rpm)
[0039] 4. Add 1.2 g of epoxy resin curing agent (modified isophorone diamine) and stir magnetically for 10 min (speed 300 rpm) to obtain a well-mixed uniform solution.
[0040] 5. Pour the evenly mixed solution into the spray bottle, aim the spray gun at the vertically placed slide and spray it. (The nozzle diameter is 2mm, the spray pressure is 0.3MPa, the spray distance is kept at 20cm, the spray time is 30s, and the best spray process value is selected) In order to spray evenly, the spray gun moves slowly from top to bottom.
[0041] 6. The sprayed coating was cured at room temperature (4 hours) and then placed in a drying oven (70°C) overnight (more than 12 hours).
[0042] Example 2
[0043] This example is used to explore the effect of different silica mass fractions on the performance of the finished product:
[0044] The only difference between this embodiment and embodiment 1 is that the amount of SiO2 of different masses added in step 2 is changed, and the amount of SiO2 nanoparticle powder used is modified to be 5%, 10%, 20%, 40%, and 50% of the total mass of the reaction system, respectively;
[0045] The finished products prepared with different SiO2 mass ratios were observed by electron microscope. The images obtained are as follows: Figure 1 shown.
[0046] Depend on Figure 1It can be seen that when the mass fraction of SiO2 is 5% (Figure a), a small amount of layered structure appears on the coating surface. Due to the addition of a small amount of SiO2, no obvious nanoparticles are found on the surface. As the mass fraction of SiO2 gradually increases, a rough structure gradually forms on the surface. When the mass fraction of SiO2 increases to 40% (Figure d), the coating has the flattest rough structure, and there are nano-scale SiO2 particles on the entire surface. When the mass fraction of SiO2 increases to 50% (Figure e), more pores and holes appear on the coating surface. Therefore, for SiO2, the most suitable SiO2 mass fraction for spraying is 40%, and the prepared coating surface has a uniform and smooth rough structure.
[0047] The above finished products were measured for apparent contact angle and rolling angle. The rolling angle was measured by using SINDINSDC-100 instrument; the measured contact angle and rolling angle data were recorded in Figure 2 middle.
[0048] Depend on Figure 2 It can be obtained that the apparent contact angle of the coating with a SiO2 mass fraction of 5% is 105.0°. As the SiO2 mass fraction further increases to 10% and 20%, the apparent contact angle of the coating increases to 113.1° and 140.5°, respectively. The SiO2 coatings with a mass fraction of 40% and 50% have similar apparent contact angles (161.0° and 162.0°, respectively). The rolling angles of the 40% and 50% SiO2 coatings are 2.1° and 2.3°, respectively. It can be found that the SiO2 coatings with a mass fraction of 40% and 50% have reached the standard of super-hydrophobic materials.
[0049] Example 3
[0050] This example is used to explore the effects of different spraying parameters on the performance of the finished product:
[0051] The only difference between this embodiment and the embodiment is that a variety of different spraying parameter settings are used:
[0052] In step 5, the spray gun is aimed at the vertically placed slide for spraying, and the spraying parameters used are:
[0053] The nozzle diameters are 1.5, 2, and 3 mm, the spraying pressure is controlled at 0.1 to 0.5 MPa, the spraying distance is maintained at 5 to 30 cm, and the spraying time is 5 to 60 s, and the best spraying process values are selected.
[0054] The finished products treated with various spraying parameters were tested, and the best effect was obtained when the parameters were 2mm, 0.3Mpa, 20cm, and 15s.
[0055] Example 4
[0056] This example is used to compare the performance difference between waterproof coating and non-waterproof coating:
[0057] The 40% silica coating used in Example 1 was sprayed on glass (7101) purchased from Jiangsu Feizhou Glass Plastic Co., Ltd., and then compared with the glass without spraying. The experimental results are as follows: Figure 3 The initial temperature of the experiment was room temperature.
[0058] For the glass, the contact angle of the glass in the blank experimental group was 40.5°, the rolling angle was greater than 90, the ice adhesion strength was 260.4 kPa, and the freezing time was 217 s.
[0059] Depend on Figure 3 It can be seen that under the optimal ratio, the freezing time of the SiO2 coating is greatly prolonged relative to the substrate glass, and the ice adhesion strength is greatly reduced to 89.8 kPa, reaching the standard of ice-repellent materials (less than 100 kPa).
[0060] Example 5
[0061] This example is used to compare with the existing anti-icing coating on the market:
[0062] The pcdf super hydrophobic coating available on the market was selected, mainly referring to the nano super hydrophobic coating M190 produced by Huaxia Jiahe, which has a contact angle of 153.2° and a rolling angle greater than 90°. The contact angle of the silicon oxide coating obtained in Example 1 is 161.0° and the rolling angle is 2.1°. The measurement method of the contact angle and the rolling angle refers to the measurement method of the contact angle and the rolling angle in Example 2.
[0063] After the measurement is completed, the coating coating performance that changes with time is determined. The specific experimental standard refers to GB9154-88, and the high-temperature treatment process is cancelled. The M190 super-hydrophobic coating, the coating prepared in Example 1, and the coating prepared by changing the SiO2 dosage to 60% in Example 2 are subjected to coating experiments. After coating, timing is performed according to Example 4. After 200 hours, the M190 super-hydrophobic coating falls off, and the coating prepared in Example 1 is intact. After 1200 hours, the coating prepared by changing the SiO2 dosage to 60% in Example 2 desorbs. After 2000 hours, the coating is scraped off with a scraper. There are a certain amount of scratches and surface depressions and pits on the glass of the M190 super-hydrophobic coating experimental group. There are certain scratches on the glass of the coating experimental group prepared by changing the SiO2 dosage to 60% in Example 2. The damage to the glass surface is the glass damage caused by direct exposure during the working time, while the glass surface of the coating experimental group in Example 1 is smooth and intact, and there is no glass damage caused by coating peeling during the working time.
[0064] The coating prepared in Example 1 has better adhesion performance and longer working time than M190. The coating prepared in Example 1 has better adhesion to the glass and better protection effect on the glass than M190. Our invention has significant advantages over time because it can maintain good adhesion and anti-icing effect over time.
[0065] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an anti-icing agent based on silicon dioxide, characterized in that: The preparation of the anti-icing agent comprises the following steps: Put 25 parts by weight of ethyl acetate and 0.8 parts by weight of FAS-17 into a beaker; Add ethyl acetate and SiO2 nanoparticle powder with a particle size of 7-40 nm, which accounts for 40% of the total weight of the FAS-17 system, and stir magnetically at a speed of 300 rpm for 10 min, and then disperse ultrasonically for 10 min, wherein the ultrasonic dispersion has a frequency of 20 kHz, a power of 500 watts, and an operating temperature of 25°C; Add 4 parts by weight of epoxy resin and 3 parts by weight of fluorosilicone resin, and stir magnetically at a speed of 300 rpm for 25 min; 1.2 g of modified isophorone diamine was added, and magnetic stirring was performed at a speed of 300 rpm for 10 min to obtain a well-mixed uniform solution, which was the silica-based anti-icing agent; The coating prepared by the anti-icing agent prolongs the freezing time to 1600s.
2. The method for preparing a silicon dioxide-based anti-icing agent according to claim 1, characterized in that: The silicon dioxide-based anti-icing agent is placed in a spray device and sprayed on a glass material to form a silicon dioxide-based anti-icing coating.
3. The method for preparing a silicon dioxide-based anti-icing agent according to claim 2, characterized in that: The nozzle diameter of the spray device is 1.5, 2, or 3 mm, the spraying pressure is controlled at 0.1 to 0.5 MPa, the spraying distance is maintained at 5 to 30 cm, and the spraying time is 5 to 60 s.
4. The method for preparing a silicon dioxide-based anti-icing agent according to claim 2 or 3, characterized in that: The spraying on the glass material has a nozzle diameter of 2 mm, a spraying pressure of 0.3 MPa, a spraying distance of 20 cm, and a spraying time of 30 s.
Citation Information
Patent Citations
Corrosion-resistant super-hydrophobic coating applied to icing prevention of insulator and preparation method thereof
CN111675957A